Water Stewardship and Rescaling Management of Transboundary Rivers in the Alberta-Montana Borderlands. Issue 2 (15th March 2019) - Belanger, Yale D.
ABSTRACT: Surface water access in northern Montana and southern Alberta is an historic political and economic concern that continues to spark contentious debate. It has however also led to several innovative attempts to reconcile differences through regional cooperation in management of transboundary rivers. One attempt—the formation of a Joint Initiative Team (JIT) in 2008 (to 2011) to investigate opportunities for each jurisdiction to improve shared water access of the St. Mary and Milk River systems—failed in its efforts to rescale the Alberta-Montana borderlands water management model. This paper explores this development, and adds to the literature by presenting a study evaluating the JIT's attempt, and the factors leading to its demise. These lessons will be of interest to scholars interested in similar issues in other border areas.